DEVELOPING SPEAKING SKILLS THROUGH INTERACTIVE CLASSROOM ACTIVITIES - Behruzkhon Yuldoshev Behzod ugli (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
This article explores the role of interactive classroom activities in developing speaking skills among learners of English as a foreign language (EFL). The study emphasizes the importance of communicative competence, active participation, and student-centered learning. Various interactive techniques such as role-play, group discussions, debates, and problem-solving tasks are analyzed for their effectiveness in enhancing fluency, accuracy, and confidence. The paper concludes that interactive activities not only improve language proficiency but also foster collaboration, motivation, and critical thinking.